The Effect Of Voltage And Time On Oxide Nanotubes Of Titanium Alloy By Anodizing For Metal Implant - Shamsuddin, Hanis (Universiti Sains Malaysia, 2022)
The Ti-Nb alloys have been widely studied due to their high biocompatibility and excellent mechanical properties for biomedical applications. The objective of this study is to study the effect of the anodization time and the enhancement of the bioactivity. TiO2 nanotubes is achieve by electrochemical anodizing. Nanotubes with different size of diameter and length were grown on Ti-Nb substrates with kept constant 10 V and 30 V at 5 min, 35 min and 65 min via electrochemical anodization. Scanning electron microscopy (SEM) imaging shows that vertically aligned nanotubular structures form on the surface of Ti-Nb alloy substrates. The anodizing voltage and time are influencing the diameter and length of nanotubes. XRD analysis confirmed that there is the formation of TiO2 layer and β phase titanium. The different of diameter and length of nanotubes can affect the properties of the Ti-Nb alloy such as corrosion resistance and mechanical. Anodizing at 30 V for 35 minutes and 65 minutes results in nanotubes with diameters of 45.53 nm and 50.66 nm, respectively. Anodizing at 30 V for 35 minutes and 65 minutes results in nanotubes with lengths of 1225.77 nm and 2250 nm. Anodizing at 10 volts for 35 minutes and 65 minutes produces nanotubes with diameters of 20.18 nm and 21.64 nm. The length of the nanotube is 106.98 nm for anodizing at 10 V for 35 minutes and 201.13 nm for 65 minutes. The surface of Ti-Nb anodized at 30 V promoted enhance cell growth as the time anodizing is increase. The application of TiO2 nanotubes is improves cell adhesion which is important in the biomedical application.